Anthelmintic Activity of Ethanolic Extract of Syzygium samarangense (Blume) Merril & Perry - Gayen, Projit Roy; Hossain, ASM Monjur Al; Saifuzzaman, Md; Faroque, ABM (Dhaka University Journal of Pharmaceutical Sciences, 2016)
Abstract not available Dhaka Univ. J. Pharm. Sci. 15(1): 109-111, 2016 (June)